Astrogliosis in the cerebral cortex of gerbils after long-term exposure to 1,1,1-trichloroethane. - Rosengren, Lars E.; Aurell, A.; Kjellstrand, P.; Haglid, Kenneth G. (Scandinavian Journal of Work, Environment & Health, 1985)
Mongolian gerbils (Meriones ungiculatus) were continuously exposed by inhalation to 1,1,1-trichloroethane at 70, 210, or 1 000 ppm for three months, followed by a four-month postexposure solvent-free period. Concentrations of two astroglial proteins, S-100 and glial fibrillary acidic (GFA) protein, were then determined in different regions of the cerebral cortex. The main biochemical alterations induced after exposure to 210 and 1 000 ppm of 1,1,1-trichloroethane demonstrated a pronounced change in gerbil brain; increased concentrations of GFA protein were found in the cerebral sensorimotor cortex at both these exposure levels, an occurrence indicating astrogliosis in this brain region. These results suggest that 1,1,1-trichloroethane should not be regarded as harmless, particularly regarding neurotoxicity, as previously claimed.
Keywords: 1,1,1-trichloroethane